The Global, Regional, and National Burden of Tracheal, Bronchus, and Lung Cancer Caused by Smoking: An Analysis Based on the Global Burden of Disease Study 2021 - Jingting Zhang; Jincheng Tang; Renyi Yang; Siqin Chen; Huiying Jian; Puhua Zeng (Annals of Global Health)
Background: Smoking is the primary risk factor for tracheal, bronchus, and lung (TBL) cancer. Objective: This study aims to explore the epidemiological trends of smoking-attributable TBL cancer from 1990 to 2021. Methods: Mortality and disability-adjusted life-years (DALYs) data for smoking-related TBL cancer from 1990 to 2021 were sourced from the Global Burden of Disease Study (GBD) 2021. Estimated annual percentage changes (EAPCs) were calculated to evaluate trends in age-standardized mortality rates (ASMRs) and age-standardized DALY rates (ASDRs). Additionally, the relationship between disease burden, EAPCs, and the sociodemographic index (SDI) was assessed. Findings: Compared with 1990, both the mortality and DALYs due to smoking-related TBL cancer substantially increased by 2021. However, during this period, ASMR [EAPC: −0.97; 95% confidence interval (CI): −1.05 to −0.89] and ASDR (EAPC: −1.29; 95% CI: −1.37 to −1.22) demonstrated a downward trend. ASMR and ASDR in females were consistently lower than in males. In 2021, East Asia had the highest ASMR, while Central Europe recorded the highest ASDR, with Greenland exhibiting the highest ASMR and ASDR at the national level. Nationally, ASMR for smoking-related TBL cancer in 2021 showed a positive correlation with SDI, while the EAPC of both ASMR and ASDR from 1990 to 2021 displayed a negative correlation with SDI. Furthermore, in 2021, the greatest number of deaths from smoking-related TBL cancer occurred in individuals aged 70–74, while DALYs were highest in the 65–69 age group. Conclusions: The burden of smoking-related TBL cancer varies across age, sex, geography, and SDI regions. Tailored public health interventions aligned with these epidemiological characteristics are essential for alleviating the disease burden.